Good business? The struggles for regulating ESG disclosure - David Monciardini (Oñati Socio-Legal Series, 2011)
During the last decade, the regulation of corporate social and environmental disclosure and reporting has gradually but steadily emerged. What explains its emergence at different levels of regulation and through varying modes of governance? Which political and socio-economic actors are involved? Who has benefitted from its emergence? The onset of the current economic and sustainability crisis has shown the need for a more ‘regulated capitalism’ and called for a re-assessment of dominant ideas about ‘CSR’ and ‘corporate governance’. Better transparency and disclosure have often been indicated as a solution to this impasse.